(untitled) (Revista Internacional de Folkcomunicação, 2020)
This study had as general objective to understand the narratives present in the sung rites the personalities of the entities of Exu represented. And, as specific objectives: to identify the narrative processes of the messages contained in the lyrics of the sung points and to relate the narrative processes with the personality characteristics of the sung points. The methodological proposal focuses on the narratives of the lyrics of the sung points of Exu and Pombo turns. Observing the attributes narrated in the points with the support of analyzing the three narrative categories by Motta (2013). It is concluded that both the Exus and the Pombogiras, keep similar characteristics, different words can be used to qualify them, however, the meanings are equivalent. Exus; Pombogiras; Sung points; Narrative